A study on the toxicity of zinc to oyster (Saccostrea iredalei). - Talabucon, Joy Arnold E (1996.)
The acute toxicity of zinc was studied using the slipper-shaped oyster, Saccostrea iredalei. A 96-hour bioassay was conducted using concentration of 10, 20, 30 40 ppm ZnSo4.7H2o respectively. The average LC50 of Trial 1, 2 & 3 at 96 hours were 25, 25.5, 21.6 respectively.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Oysters